Evaluation of Pancreatic Steatosis in Patients with Celiac Disease - Tarhan, Ahmet; Gökden, Yasemin; Aydemir, Sinem; Önol, Suzan; Özek, Fatma Zülal (Turkish Journal of Gastroenterology, 2025)
Background/Aims: Celiac disease, a chronic autoimmune disorder, has been reported to be associated with pancreatic involvement, including exocrine pancreatic insufficiency, pancreatitis, and cystic fibrosis. The aim of this cross-sectional study was to determine the frequency of pancreatic steatosis (PS) in patients with celiac disease and compare it with that in healthy controls. Materials and Methods: Sixty patients with celiac disease and 60 healthy participants were included in this study. Biochemical and hematological parameters were collected from all participants. Hepatic steatosis (HS) and PS were diagnosed by ultrasonography and were compared between the groups. Results: Age, gender, and body mass index were similar between the groups (P > .05). Pancreatic steatosis (81.7%) and HS (66.7%) were more prevalent in the celiac group compared to healthy controls (P < .001). A positive and significant correlation was found between PS and HS in the celiac group (rho = 0.464, P < .05). Hepatic steatosis and PS did not differ between tissue transglutaminase Immunoglobulin A (IgA)-positive and -negative patients with celiac disease (P > .05). No differences in HS or PS were found between celiac patients who adhered to a gluten-free diet and those who did not (P > .05). Conclusion: Celiac disease may be associated with an increased risk of HS and PS. Cite this article as: Tarhan A, Gökden Y, Aydemir S, Önol S, Özek FZ. Evaluation of pancreatic steatosis in patients with celiac disease. Turk J Gastroenterol. Published online October 20, 2025. doi:10.5152/tjg.2025.25069.